Describing the health profile of Singaporeans : A longitudinal study. - Chong, Natalie Ching Hsia. (2008)
This study aims to describe the health status of Singaporeans using a Multi-Attribute Health Status Classification (MAHSC) system. It forms part of a larger research on health care costs and health status measurement. Data was collected through mailed questionnaires. A longitudinal analysis was carried out using data collected from the same respondents this year and last year. The relationship between health status and various demographic factors was also investigated.